Lycopene as a Natural Antioxidant Used to Prevent Human Health Disorders - Muhammad Imran; Fereshteh Ghorat; Iahtisham Ul-Haq; Habib Ur-Rehman; Farhan Aslam; Mojtaba Heydari; Mohammad Ali Shariati; Eleonora Okuskhanova; Zhanibek Yessimbekov; Muthu Thiruvengadam; Mohammad Hashem Hashempur; Maksim Rebezov (MDPI AG, 2020)
Lycopene, belonging to the carotenoids, is a tetraterpene compound abundantly found in tomato and tomato-based products. It is fundamentally recognized as a potent antioxidant and a non-pro-vitamin A carotenoid. Lycopene has been found to be efficient in ameliorating cancer insurgences, diabetes mellitus, cardiac complications, oxidative stress-mediated malfunctions, inflammatory events, skin and bone diseases, hepatic, neural and reproductive disorders. This review summarizes information regarding its sources and uses amongst different societies, its biochemistry aspects, and the potential utilization of lycopene and possible mechanisms involved in alleviating the abovementioned disorders. Furthermore, future directions with the possible use of this nutraceutical against lifestyle-related disorders are emphasized. Its protective effects against recommended doses of toxic agents and toxicity and safety are also discussed.